Effect of Used Coffee Grounds on Larval Mortality of Aedes aegypti L. (Diptera: Culicidae): Suspension Concentration and Age versus Efficacy - Guirado, Marluci Monteiro; Bicudo, Hermione Elly Melara de Campos (BioAssay, 2009)
In a previous study, used coffee ground affected the larval development of Aedes aegypti. In this work, we evaluated the duration of the effect on larval mortality of aqueous suspensions of used coffee ground at 75, 150, 250 and 300 mg/ml concentrations. The larval mortality was followed daily, in the experimental breeding sites; 300 mg/ml was the most efficient concentration, producing 100% of larval mortality until nine days after preparation. These results were observed in experiments in which the larvae remained free in the vials, making contact both the used coffee ground deposits and the supernatant liquid, and also in experiments in which the larvae were maintained in a sieve of fine screen immersed in the liquid part of the suspension. Thus, although the elimination of the breeding sites remains being the best way to control Aedes aegypti population size, the results obtained herein reinforces the validity of considering used coffee ground preparations as possible auxiliary in the alternative control of this mosquito, mainly in the gardens. Used coffee ground has the advantage of being free of cost, since it is the powder that is left after coffee has been filtered out to drink.